CHA2DS2‐VASc score and adverse outcomes in patients with heart failure with reduced ejection fraction and sinus rhythm. (21st July 2016) - Ye, Siqin; Qian, Min; Zhao, Bo; Buchsbaum, Richard; Sacco, Ralph L.; Levin, Bruce; Di Tullio, Marco R.; Mann, Douglas L.; Pullicino, Patrick M.; Freudenberger, Ronald S.; Teerlink, John R.; Mohr, J.P.; et al.
Abstract: Aims: The aim of this study was to determine whether the CHA2 DS2 ‐VASc score can predict adverse outcomes such as death, ischaemic stroke, and major haemorrhage, in patients with systolic heart failure in sinus rhythm. Methods and results: CHA2 DS2 ‐VASc scores were calculated for 1101 patients randomized to warfarin and 1123 patients randomized to aspirin. Adverse outcomes were defined as death or ischaemic stroke, death alone, ischaemic stroke alone, and major haemorrhage. Using proportional hazards models, we found that each 1‐point increase in the CHA2 DS2 ‐VASc score was associated with increased hazard of death or ischaemic stroke events [hazard ratio (HR) for the warfarin arm = 1.21, 95% confidence interval (CI) 1.13–1.30, P < 0.001; for aspirin, HR = 1.20, 95% CI 1.11–1.29, P < 0.001]. Similar increased hazards for higher CHA2 DS2 ‐VASc scores were observed for death alone, ischaemic stroke alone, and major haemorrhage. Overall performance of the CHA2 DS2 ‐VASc score was assessed using c ‐statistics for full models containing the risk score, treatment assignment, and score–treatment interaction, with the c ‐statistics for the full models ranging from 0.57 for death to 0.68 for major haemorrhage. Conclusions: The CHA2 DS2 ‐VASc score predicted adverse outcomes in patients with systolic heart failure in sinus rhythm, with modest prediction accuracy.